Kompres hangat dengan Botol Kaca sebagai Alternatif menurunkan Nyeri Punggung bawah pada Ibu hamil Trimester III - Sumantri; Satiyem (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2024)
Back pain during the third trimester generally occurs because the back of pregnant women has to support a heavier body. This pain can also be caused by the relaxin hormone which relaxes the joints between the bones in the pelvic area. Looseness of these joints can affect body posture and trigger back pain. The prevalence of low back pain in pregnant women reaches 49% and 80-90% of pregnant women who experience back pain say they do not do anything, and 10-20% seek medical treatment. One way to treat back pain with non-pharmacological therapy is a warm compress using a glass bottle, because a warm compress using a glass bottle can provide a feeling of comfort, warmth and the reaction lasts longer. To find out the effect of a warm compress using a glass bottle on reducing lower back pain in pregnant women III trimester in the work area of ​​the South Klaten Community Health Center. This type of quantitative research is a quasi-experimental design with a one group pretest and serial posttest design. Total sampling data collection technique was obtained. Data analysis used parametric statistics because the data was normally distributed using Paired t-Test with a significance level of p<0.05. The reduction in low back pain levels carried out by the first intervention (post test 1) was an average of 5.514, after the second intervention was carried out (post test 2 ) an average of 4.511, and after the third intervention (post test 3) an average of 3.425. And the most significant reduction was in the second intervention with a t value of 29.979. There was a significant influence on reducing lower back pain for third trimester pregnant women in both the first, second and third interventions with a p value of 0.000 (p <0.005). However, the most significant effect was in the second intervention with a t value of 29.979